The Program of Professional Development for Psychology Students “My Career” - Filatova, Olga; Filatov, Vitaliy (Journal of Education, Technology and Computer Science, 2019)
The article is devoted to the problem of professional development of an individual during their studies at the University. On the basis of empirical data the authors developed a program of psychological support for professional development of Psychology students and describe it in the paper.